JURISDICTION OF THE COURT OF THE EURASIAN ECONOMIC UNION:LIMITS AND DEVELOPMENT PROSPECTS (VERITAS LEGIS JOURNAL, 2026)
This article examines the jurisdiction of the Court of the Eurasian Economic Union (the Court and the EAEU/Union, respectively), its current boundaries, and prospects for further development. In the current context of the development of integration processes within the EAEU, an important role is played by effective mechanisms for resolving disputes and ensuring the uniform application of Union law. This article examines the legal basis for the Court's activities, its jurisdiction, procedures for seeking judicial protection, and interpretation of law. It also examines prospects for expanding the Court's powers, taking into account the growing need for legal protection for participants in the integration process and the increased effectiveness of the EAEU legal system. The paper draws on the practical experience of the EAEU Court and legal positions developed by other courts of integration associations to support its theses. The work aims to identify areas for improving the EAEU Court's activities as a key institution in ensuring legal stability and the integration legal order.
Keywords: Eurasian Economic Union; EAEU; Court of the EAEU; competence of the Court of the EAEU; integration law